Cyber crimes against women in India - Halder, Debarati (SAGE, 2017)
Introduction -- Freedom of speech and expression in the cyber space -- Trolling and gender bullying -- Online grooming -- Privacy infringement -- Online sexual offences -- Right to be forgotten: liability of the service providers -- Procedural practices for investigation, prosecution, arrest and detention -- Combating of the offences